Pilot-scale study of a structured bed reactor for nitrogen and organic matter removal from sanitary sewage: advances and design challenges (Research, Society and Development, 2021)
Simultaneous nitrification and denitrification (SND) is a process that can remove both nitrogen and organic matter in a single unit. Several bench-scale studies show that the structured bed reactors (STBR) subjected to recirculation and intermittent aeration have achieved a good performance for SND treating different types of wastewater. Thus, this study took a step forward and evaluated the efficiency and stability of treating domestic sewage in a pilot-scale STBR. COD removal efficiencies higher than 87% were achieved in the whole experimental period. The highest Total-N removal efficiency was approximately 74 ± 7% by adopting a hydraulic retention time (HRT) of 47.2 h and intermittent aeration (2 h aerated and 1 h non-aerated). The setup of the aeration system was an important mechanism to ensure the optimal balance between nitrification and denitrification in a pilot-scale system.